Jail inmates, 1991 - Jankowski, Louis W. (Bureau of Justice Statistics)
The survey obtained data from 1,124 jails in 799 jurisdictions, approximately one-third of all jails. The jails surveyed are facilities administered by local officials and designed to hold persons for more than 48 hours but usually for less than 1 year. At mid-year 1991, local jails in the United States held an estimated 426,479 persons, a 5.2-percent increase from midyear 1990. The average daily jail population for the year ending June 28, 1991, was 422,609, a 3.6-percent increase since 1990. Overall jail occupancy was 101 percent of the rated capacity of the Nation's jails. Males constituted 90.7 percent and females 9.3 percent of all jail inmates. White non-Hispanics were 41.1 percent of the local jail population; black non- Hispanics, 43.4 percent; Hispanics, 14.2 percent; and non- Hispanics of other races, 1.2 percent of all inmates reporting race. Unconvicted inmates were 51 percent of the adults being held in jails. The overall occupancy rate was 107 percent of rated capacity. Rated capacity increased by 9 percent, an expansion nearly twice the rate of inmate population growth. Twenty-seven percent of the jurisdictions had at least one jail under court order to limit population; 30 percent were under court order to improve one or more conditions of confinement. Data are also provided on inmate deaths. 12 tables